The origin of subdwarf B star - I: The formation channels - Han, Z; Podsiadlowski, P; Maxted, P; Marsh, T; Ivanova, N (Oxford University Press, 2002)
Subdwarf B (sdB) stars (and related sdO/sdOB stars) are believed to be helium-core-burning objects with very thin hydrogen-rich envelopes. In recent years it has become increasingly clear from observational surveys that a large fraction of these objects are members of binary systems. To understand their formation better, we present the results of a detailed investigation of the three main binary evolution channels that can lead to the formation of sdB stars: the common-envelope (CE) ejection channel, the stable Roche lobe overflow (RLOF) channel, and the double helium white dwarfs (WDs) merger channel. The CE ejection channel leads to the formation of sdB stars in short-period binaries with typical orbital periods between 0.1 and 10 d, very thin hydrogen-rich envelopes and a mass distribution sharply peaked around ∼0.46 M⊙. On the other hand, under the assumption that all mass transferred is soon lost, the stable RLOF channel produces sdB stars with similar masses but long orbital periods (400–1500 d) and with rather thick hydrogen-rich envelopes. The merger channel gives rise to single sdB stars whose hydrogen-rich envelopes are extremely thin but which have a fairly wide distribution of masses (0.4−0.65 M⊙). We obtained the conditions for the formation of sdB stars from each of these channels using detailed stellar and binary evolution calculations where we modelled the detailed evolution of sdB stars and carried out simplified binary population synthesis simulations. The observed period distribution of sdB stars in compact binaries strongly constrains the CE ejection parameters. The best fits to the observations are obtained for very efficient CE ejection where the envelope ionization energy is included, consistent with previous results. We also present the distribution of sdB stars in the Teff−log g diagram, the Hertzsprung–Russell diagram and the distribution of mass functions.